Tindak tutur ilokusi dalam upacara adat perkawinan batak toba di Desa Sitoluama - Erika Lestari Sipayung; Lisa Septia Dewi br. Ginting (Jurnal Komunitas Bahasa, 2023)
The purpose of this research is to identify the types of illocutionary speech acts used in the Toba Batak traditional wedding ceremony in Sitoluama Village, as well as the meaning and method of delivery. The data for this study came from speeches given at weddings and were collected using a qualitative descriptive approach. The theory of pragmatic speech acts is applied in this statement. A total of 42 illocutionary speech acts, 16 representative speech acts, 17 directive speech acts, 7 expressive speech acts, 0 commissive speech acts, and 2 declarative speech acts were identified as the result of the data collection process.